2006
DOI: 10.1111/j.1445-2197.2006.03728.x
|View full text |Cite
|
Sign up to set email alerts
|

A RAT MODEL OF POLYPROPYLENE GRAFT INFECTION CAUSED BY STAPHYLOCOCCUS EPIDERMIDIS

Abstract: Incubation of polypropylene grafts with slime-producing S. epidermidis for 2 and 24 h in the pre-application period achieved the occurrence of a standardized graft infection. Prophylactic use of teicoplanin and rifampicin decreased the infection rates. We propose to use this reproducible and reliable animal model of graft infection in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…ePTFE is more hydrophobic and less porous than polypropylene [26]. The deformation of the internodal filaments and creation of fissures in the ePTFE microstructure by the bacteria increases bacterial attachment [17,26]. It has been reported that microorganisms adhere to and penetrate between the internodal filaments of PTFE, altering its internal structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ePTFE is more hydrophobic and less porous than polypropylene [26]. The deformation of the internodal filaments and creation of fissures in the ePTFE microstructure by the bacteria increases bacterial attachment [17,26]. It has been reported that microorganisms adhere to and penetrate between the internodal filaments of PTFE, altering its internal structure.…”
Section: Discussionmentioning
confidence: 99%
“…The surface free energy of ePTFE may be related to the difference observed. ePTFE is more hydrophobic and less porous than polypropylene [26]. The deformation of the internodal filaments and creation of fissures in the ePTFE microstructure by the bacteria increases bacterial attachment [17,26].…”
Section: Discussionmentioning
confidence: 99%
“…Ancak önemli bir diğer amacı da multienstütisyonel, multidisipliner, translasyonel araştırma konusunda araştırma grubunun her basmaktaki üyelerine büyük bir öğrenim ve deneyim kazanma süreci sağlama-sıdır. Bu (4) . Biyofilm çalış-maları için uygun bakteriyolojik yöntemleri değerlendirmek için sonikasyon ve vorteksleme yöntemlerini karşılaştırdık (2) .…”
Section: Derlemeunclassified
“…0.5 [11]. This solution was then used to inoculate 3-0 coated polyglactin910 (Vicryl ® , Ethicon, Somerville, NJ) by incubating the suture in the E. coli suspension for 2 h at 4 C [12].…”
Section: Introductionmentioning
confidence: 99%